h-prime and h-semiprime ideals in Γ_N-semirings and Matrix Semiring (arrayllR&Γ S&Larray) - Sujit, Kumar Sardar; Bibhas, Chandra Saha (Armenian Journal of Mathematics, 2009)
n this paper we show that h-prime and h-semiprime ideals in a Nobusawa Γ-semiring are preserved by the functions ^*’( ), ^+’( ), ^*( ), ^+( ), Γ ( ) and S( ). This preservation property is then used to characterize h-prime and h-semiprime ideals in matrix semiring (arrayll R & Γ S & L array ). Moreover, characterization theorems of h-regular and H-Noetherian Γ-semirings have been obtained.